(untitled) (Journal of the College of Basic Education, 2024)
The interrogative is one of the important linguistic mechanisms in argumentation because it carries argumentative energy that the speaker can use to influence the recipient, control his mind, and direct the speech toward what he wants and not what the recipient wants. This energy comes from the implicit assumptions that the interrogation carries, and based on that research to demonstrate the effect of the interrogative. As one of the most important linguistic mechanisms for pilgrims, through the implicit assumptions it carries in the collection (Our Glories Speak and Other Poems by the Poet Mufdi Zakaria). This research was built on two sections preceded and followed by a conclusion. The first of the two sections was an introductory pause on the terms (Pilgrims and Questions), and the second was an applied study. Because of the implicit assumptions that the question carried in the aforementioned collection, I took in writing the research from multiple linguistic sources and references that included language and grammar books by ancient and modern scholars, as well as linguistic dictionaries.